Penerapan Pijat Oksitosin Oleh Suami Terhadap Kelancaran Produksi ASI Pada Ibu Post Partum Di Puskesmas Kebakkramat 1 Kabupaten Karanganyar - Evi Novitasari; Maryatun Maryatun (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: The post partum period is the period in the mother which starts from the day of birth up to 6 weeks after birth during this time the mother is obliged to provide breast milk to the baby. WHO data shows that 46% of post partum mothers do not give exclusive breastfeeding during the first 6 months because of problems with milk insufficiency. The problem of failure to give exclusive breastfeeding to babies that needs attention is because mothers who experience breast milk are not smooth. Efforts that can be made to increase the smoothness of breast milk production can be by oxytocin massage by the husband. Objective: To find out the results of implementing oxytocin massage on the smoothness of breastfeeding in post partum mothers in Kebakkramat District, Karanganyar Regency. Method: This type of research is descriptive in the form of a case study. Results: The smooth expulsion of breast milk before the application of Oxytocin Massage by the husband shows that breast milk is not smooth. The smoothness of breastfeeding after an oxytocin massage by the husband for the two respondents showed smooth breastfeeding. There was a smooth development of ASI during the 3 days of applying oxytocin massage. There was a change in the smoothness of milk production in the two respondents after the application of Oxytocin Massage or Increased Breast Milk. Conclusion: There was a change in the smoothness of breastfeeding before and after the oxytocin massage was performed on the two post partum mother respondents.